Cover Image, Volume 21, Issue 6 - Gill, Fenella J. (Health Expect, 2018)
The cover image is based on the Original Research Paper Barriers and facilitators to implementing a process to enable parent escalation of care for the deteriorating child in hospital, by Fenella J. Gill PhD, RN, FACCCN et al., DOI 10.1111/hex.12806. [Image: see text]